2013
DOI: 10.1007/s00402-013-1705-x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of rotational deformity on patellofemoral parameters following the treatment of femoral shaft fracture

Abstract: The results of this study revealed that more than 10° of external rotation deformity could cause a detoriation in the patellofemoral scores. Anatomic reduction of the fracture site should be performed as soon as possible and external rotational deformities should especially be avoided in order to prevent patellofemoral malalignment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 30 publications
0
25
0
Order By: Relevance
“…We reported that femur malrotation > 10° was associated to an increase in patellar tilt and congruence angle. Yildirim et al reported the effect of femoral deformity following femoral shaft fracture, underlying the role of external malrotation > 10° [6]. They observed deterioration in the PF scores and medial patellar tilt for patient with such deformities.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We reported that femur malrotation > 10° was associated to an increase in patellar tilt and congruence angle. Yildirim et al reported the effect of femoral deformity following femoral shaft fracture, underlying the role of external malrotation > 10° [6]. They observed deterioration in the PF scores and medial patellar tilt for patient with such deformities.…”
Section: Discussionmentioning
confidence: 99%
“…PF changes in axial alignment are clinically relevant, especially for anterior knee pain and patellar instability [4,6,12]. However, the influence of stress distribution in anterior pain is controversial, because of the participation of the involved biological factors.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…9 Yildirim et al stated that patellofemoral malalignment following closed IMN could cause pain and decreased patellofemoral scores. 28 Ozgur consistently found patients with rotational malalignment complaining of anterior knee pain while climbing stairs and attributed it to imbalance of the patellofemoral mediolateral force secondary to a torsional deformity of the femur. 29,30 In our study no significant difference was noted between the groups in terms of HHS probably because of the limited number of cases, short duration of follow up and absence of extreme rotational malalignment >20 0 .…”
Section: Resultsmentioning
confidence: 99%